The concept of competitive productivity (CP): a linguistic investigation. Issue 1 (29th September 2020) - Hoadley, Susan
Abstract : Purpose: The paper presents an investigation into the validity and robustness of the concept of competitive productivity (CP) using linguistic analysis and theory to explore the foundational CP concepts and the relationships between them. Design/methodology/approach: The aim of this paper is to make a theoretical contribution to the conceptualisation of CP in order to inform its understanding, measurement and application. Findings: The investigation indicates the relevance of three dimensions (instantiation, stratification and system) to understand CP as a complex, multidimensional system. Instantiation both clarifies CP as a multilevel system and highlights the need for an additional dimension(s) to understand the relationship between national, firm and individual CP (NCP, FCP and ICP). In combination, the two dimensions of stratification and system model CP as a series of nested strata (theory/models, concepts, constructs, variables and measures) through which marketing and management theory and knowledge is created and demonstrate how the options at each level can be articulated as system networks. Research limitations/implications: Managing the complexity of CP by mapping different aspects along different dimensions and, in doing so, better understanding the nature of and relationships between different phenomena within the domain can potentially inform future qualitative and quantitative research in business studies and beyond. Originality/value: The paper uses a novel, interdisciplinary approach to demonstrate the existence of CP as a complex, multidimensional system, where such dimensions inform the understanding, measurement and application of CP, and so is of value to marketing and management researchers and practitioners.